If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-5(3x-4)=3(x-2)
We move all terms to the left:
7-5(3x-4)-(3(x-2))=0
We multiply parentheses
-15x-(3(x-2))+20+7=0
We calculate terms in parentheses: -(3(x-2)), so:We add all the numbers together, and all the variables
3(x-2)
We multiply parentheses
3x-6
Back to the equation:
-(3x-6)
-15x-(3x-6)+27=0
We get rid of parentheses
-15x-3x+6+27=0
We add all the numbers together, and all the variables
-18x+33=0
We move all terms containing x to the left, all other terms to the right
-18x=-33
x=-33/-18
x=1+5/6
| 10^6x+10^5=10^6 | | 6x-14=-3x+17 | | 7h=6h | | 3n=-60,n= | | (1089*x^2)-7623*x+13034=0 | | x/4=(2x/3)+(5/6) | | -3x+7=2-x | | 1=e+9 | | -3/7(3w-2)=-21 | | u-1.1=8.92 | | x-8.2=5.7 | | (x/2)+2=(1/10) | | 24x-21=-3 | | y+2.19=7.76 | | 24x-21=-3{1-6x} | | 9a-16=7a-1 | | 2x2+9x+8=0 | | 8-0.5x-1=-(x+4) | | 8-1/2x-1=-(x+4) | | 3n−5=7n+11 | | 8-1/2x-1=-(x+4 | | -.167x+2=7 | | -3|5x+2=7 | | -112+8x=192 | | 4/7=7/x | | 55÷2x=80 | | 3(6q-9)+7(q+4)=5(6q+8)-5(q+1) | | (5x/10)=(-19/10) | | -3(x-4)=-39-9) | | 1/2+2/5t*1=1/5t+t | | x+5=-3+7 | | 2x5-2=8 |